ANTIHYPERURICEMIA ACTIVITY OF ETHANOL EXTRACT AND FRACTIONS OF AZADIRACHTA INDICA LEAF IN VIVO AND MECHANISM OF ACTION OF ACTIVE FRACTIONS IN VITRO - Deden Winda Suwandi; Anas Subarnas; Sri Adi Sumiwi (Fakultas MIPA Universitas Garut, 2021)
Azadirachta indica, A.,Juss is a medicinal plant that is used traditionally for some disease, especially its leaves to treat a rheumatic diseases and lower blood uric acid levels. This study was carried out to examine antihyperuricemia activity of ethanol extract, water fraction, ethyl acetat fraction and n-hexane fraction of the A. Indica leaves in male mice of Swiss-Webster strain. Extract and fraction doses used were 250 and 500 mg/kg of body weight and the doses of allopurinol as a standard drug was 13 mg/kg of body weight. The tests were conducted on mice suffering from hyperuricemia induced by potassium oxonat at adose of 300 mg/kg of body weight intraperitoneally and chicken liver juice orally. Measurement of blood uric acid levels were performed using an Easy Touch® every hour for 4 hours after being given test preparations. The results showed that the ethanol extract and the fractions lowered blood uric acid levels in the same way as allopurinol did. The n-hexane fractions at the all doses showed the highest activity, followed by ethanol fraction, and water fraction at the dose of 250 mg/kg at the 4th hour. These results illustrated that the A. Indica leaves might be potential to be used as antihyperuricemia. The active compounds which possibly reduce blood uric acid levels in mice are believed to be flavonoid or polyphenolic compounds because they are reported to be able to inhibit the action of the xanthine oxidase enzyme that converts purines into uric acid. Then, the most active fraction, n-hexane fraction, was tested for its inhibitory activity on xanthine oxidase enzyme to determine its mechanism of action. The results showed that the n-hexane fraction, like allopurinol, inhibited uric acid biosynthesis through inhibiting the activity of xanthine oxidase enzyme with the IC50 value of 132 μg/mL lower than that of allopurinol IC50 58.35 μg/mL. Key words: A. indica leaves, antihyperuricemia, chicken liver juice, potassium oxonat, xanthine oxidase.